UNTANGLING ACCESS: EXPLORING THE RULING RELATIONS OF LACTATION SPACES IN HIGHER EDUCATION FOR WOMEN IN DOCTORAL PROGRAMS. - Wright, Casey E.; Pawley, Alice L. (Journal of Ethnographic & Qualitative Research)
This institutional ethnographic study examined neoliberal discourses conveyed in implementing lactation space policy from the standpoints of doctoral student women. We generated level 1 data by interviewing doctoral student women to learn about their experiences accessing lactation spaces and to locate the institutional actors involved in lactation policy implementation; we then collected and analyzed institutional texts and interviews with institutional actors. Using Doucet & Mauthner's "Listening Guide" we analyzed data narratively and mapped ruling relations between texts and actors to understand policy implementation. We found participants had limited access to lactation spaces because their organization positioned them as both and neither a student and employee, contributing to a paradoxical discourse of the organization valuing research while not supporting the doctoral researchers' embodied needs. We recommend organizational improvements to support sufficient paid leave and better educate campuses about the maintenance and function of lactation facilities.